Impact of Integrated Reporting Quality Disclosure on Cost of Equity Capital in Australia and New Zealand - Hazhar Pira Sharif; Jalila Johari; Wan Fadzilah; Lau Wei Theng (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study aims to ascertain the relationship between the integrated reporting quality (IRQ) disclosures and the implied cost of equity capital (ICC) in the developed markets of Australia and New Zealand. The study provides empirical results on whether companies producing higher-quality integrated reporting (IR) under a regular process can reduce equity capital costs. This study focuses on the benefits of IR and notes that there is actually more information asymmetry between firms and investors than previously believed. The study concludes that IR plays a salient role in capital costs (when information asymmetry is greater) than cross-sectional tests. The 100 companies studied were chosen based on Standard and Poor market capitalization listed in Australia and New Zealand from 2014 until 2016. The study considered a total of 870 observations of post-implementation IR. Further, data were collected from a validated secondary database. This study showed a significant, negative relationship between IRQ and the ICC in the developed market. The results of this study encourage companies that have not yet adopted IR to do so for accelerating reduction in the ICC. Consequently, this study can help promote IR and attract more countries to implement IR policies to enhance IR research.